The Case for, and Challenges of, Human Cardiac Tissue in Advancing Phosphoprotein Research - Huang, Amanda W.; Janssen, Paul M. L. (Frontiers in Physiology, 2022)
Cardiovascular disease (CVD) and stroke affect over 92 million Americans and account for nearly 1 out of 3 deaths in the US. The use of animal models in cardiovascular research has led to considerable advances in treatment and in our understanding of the pathophysiology of many CVDs. Still, animals may not fully recapitulate human disease states; species differences have long been postulated to be one of the main reasons for a failure of translation between animals and humans in drug discovery and development. Indeed, it has become increasingly clear over the past few decades that to answer certain biomedical questions, like the physiological mechanisms that go awry in many human CVDs, animal tissues may not always be the best option to use. While human cardiac tissue has long been used for laboratory research, published findings often contradict each other, leading to difficulties in interpretation. Current difficulties in utilizing human cardiac tissue include differences in acquisition time, varying tissue procurement protocols, and the struggle to define a human “control” sample. With the tremendous emphasis on translational research that continues to grow, research studies using human tissues are becoming more common. This mini review will discuss advantages, disadvantages, and considerations of using human cardiac tissue in the study of CVDs, paying specific attention to the study of phosphoproteins.